2023
DOI: 10.1002/cssc.202300626
|View full text |Cite
|
Sign up to set email alerts
|

On the Tunability of Toxicity for Viologen‐Derivatives as Anolyte for Neutral Aqueous Organic Redox Flow Batteries

Abstract: Viologen‐derivatives are the most widely used redox organic molecules for neutral pH negative electrolyte of redox flow batteries. However, the long‐established toxicity of the herbicide methyl‐viologen raises concern for deployment of viologen‐derivatives at large scale in flow batteries. Herein, we demonstrate the radically different cytotoxicity and toxicology of a series of viologen‐derivatives in in vitro assays using model organisms representative of human and environmental exposure, namely human lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Finally, the kinetic analyses demonstrated that the charge storage of the NDI-2Vi electrode predominantly depends on the surface-controlled redox process, providing high-rate performance even in the highly concentrated electrolyte. Although methyl viologen is a widely used herbicide due to high toxicity, recent studies revealed that the toxicity of viologen derivatives can significantly be alleviated by substituting large and bulky groups at the N-positions of viologens. Therefore, we can expect that NDI-2Vi has a low toxicity appropriate for use as an energy storage material.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the kinetic analyses demonstrated that the charge storage of the NDI-2Vi electrode predominantly depends on the surface-controlled redox process, providing high-rate performance even in the highly concentrated electrolyte. Although methyl viologen is a widely used herbicide due to high toxicity, recent studies revealed that the toxicity of viologen derivatives can significantly be alleviated by substituting large and bulky groups at the N-positions of viologens. Therefore, we can expect that NDI-2Vi has a low toxicity appropriate for use as an energy storage material.…”
Section: Discussionmentioning
confidence: 99%
“…59 In contrast, di-polar viologens contain anionic substitutes, indicating that di-polar viologens are a safer and more environmentally friendly option. 60…”
Section: Environmental Impacts Of Viologensmentioning
confidence: 99%
“…As a traditional herbicide, the toxicity of MV and its derivatives is often ignored by the researchers in the field of AORFBs. Ventosa et al 72 evaluated the cytotoxicity and toxicology of seven viologens using the human lung carcinoma epithelial cell line (A549) and the yeast Saccharomyces cerevisiae . After the treatment at different concentrations of viologens for 24 h, the viability of the human cell line was determined by the neutral red uptake assay.…”
Section: Propertiesmentioning
confidence: 99%